Typologies of Altruistic and Financial Motivations for Research Participation: A Qualitative Study of MSM in HIV Vaccine Trials - Chin, Lisa J.; Berenson, Jacqueline A.; Klitzman, Robert L. (Journal of empirical research on human research ethics, 2016)
Questions arise concerning participants’ motives in risky studies, such as HIV vaccine trials (HVTs). We interviewed indepth 20 gay/bisexual men. Participants described both altruistic and nonaltruistic motives. Altruistic motivations emerged primarily, with nine typologies: (a) cultural, (b) community related, (c) familial, (d) religious, (e) professional, (f) political (e.g., HIV activism), (g) moral (e.g., making up for past wrongs), (h) existential (e.g., providing sense of meaning), and (i) other psychological (e.g., emotional gratification). Views of compensation varied: not a factor (55%), added incentive (25%), main motivator, but in conjunction with altruism (15%), and primary motivator (5%). HVT participants thus often have both altruistic and financial motives, and related typologies emerged. These findings have critical implications for studies on HIV, other conditions, and research ethics.